Less is More: Reducing Radiation in Hysterosalpingography Through Targeted Interventions - Belqees Yawar Faiz; Sanam Yasir; Khalid Shakeel Babar; Maryam Asghar; Mahnoor Akhtar Khan; Fatima Tanveer; Manoj Kumar; Muhammad Asif (PKLI Journal of Health Sciences, 2026)
Background:Hysterosalpingography (HSG) is used for evaluating female infertility, particularly for fallopian tube patency and uterine cavity abnormalities. It involves radiation exposure, which may pose potential risks to women of reproductive age. Therefore, optimizing radiation dose according to the ALARA principle is essential.Objective:To investigate the radiation exposure time of patients undergoing fluoroscopic hysterosalpingography (HSG) before and after implementation of interventions aimed at reducing the radiation exposure.Methods:After approval from Institutional Review Board, the study was conducted in radiology department of Shifa International hospital, Islamabad.The prospective study includes 120 female patients .The study was performed in two phases: February–May 2022 (Phase 1) and September–December 2022 (Phase 2), separated by period of interventions to achieve the fluoroscopy screening time according to National Diagnostic Reference Level (NDRL) back in 2016.Interventions includetraining the radiology residents, equipment optimization, patient counselling and improved coordination between fluoroscopic operator and assisting staff.Paired-T test was employed to compare the mean radiation exposure time in normal studies in Phase 1 with that of normal studies in Phase 2, and to also compare the mean radiation exposure time in abnormal studies in Phase 1 with that of abnormal studies in Phase 2.Results:Patients’ ages ranged between 25-35 years with an average of 30 years. The mean radiation exposure time in Phase 1 was 94.9 seconds for normal studies and 181.5 seconds for abnormal studies. In Phase 2, the mean exposure time was reduced to 45 seconds for normal studies and 46.5 seconds for 1Diagnostic Radiology, Shifa International hospital Islamabad, Pakistan.2Diagnostic Radiology, PKLI & RC, LahoreCorresponding AuthorFatima TanveerEmail: fatima.tanveer907@gmail.com PKLI Journal of Health Sciences, 20264Vol. 2, No. 1, August 2026https://pklijhs.org.pk/abnormal studies. Paired t-tests showed significant reductions in exposure times in both groups, with p-values < 0.005. Conclusion:Significant reductions in radiation exposure time were noted, highlighting the effectiveness of the interventions